Use it or lose it: tonic activity of slow motoneurons promotes their survival and preferentially increases slow fiber-type groupings in muscles of old lifelong recreational sportsmen - Simone Mosole; Ugo Carraro; Helmut Kern; Stefan Loefler; Sandra Zampieri (PAGEPress Publications, 2016)
Histochemistry, immuno-histochemistry, gel electrophoresis of single muscle fibers and electromyography of aging muscles and nerves suggest that: i) denervation contributes to muscle atrophy, ii) impaired mobility accelerates the process, and iii) lifelong running protects against loss of motor units. Recent corroborating results on the muscle effects of Functional Electrical Stimulation (FES) of aged muscles will be also mentioned, but we will in particular discuss how and why a lifelong increased physical activity sustains reinnervation of muscle fibers. By analyzing distribution and density of muscle fibers co-expressing fast and slow Myosin Heavy Chains (MHC) we are able to distinguish the transforming muscle fibers due to activity related plasticity, to those that adapt muscle fiber properties to denervation and reinnervation. In muscle biopsies from septuagenarians with a history of lifelong high-level recreational activity we recently observed in comparison to sedentary seniors: 1. decreased proportion of small-size angular myofibers (denervated muscle fibers); 2. considerable increase of fiber-type groupings of the slow type (reinnervated muscle fibers); 3. sparse presence of muscle fibers co-expressing fast and slow MHC. Immuno-histochemical characteristics fluctuate from those with scarce fiber-type modulation and groupings to almost complete transformed muscles, going through a process in which isolated fibers co-expressing fast and slow MHC fill the gaps among fiber groupings. Data suggest that lifelong high-level exercise allows the body to adapt to the consequences of the age-related denervation and that it preserves muscle structure and function by saving otherwise lost muscle fibers through recruitment to different slow motor units. This is an opposite behavior of that described in long term denervated or resting muscles. These effects of lifelong high level activity seems to act primarily on motor neurons, in particular on those always more active, i.e., on the slow motoneurons. The preferential reinnervation that follows along decades of increased activity maintains neuron and myofibers. All together the results open interesting perspectives for applications of FES and electroceuticals for rejuvenation of aged muscles to delay functional decline and loss of independence that are unavoidable burdens of advanced aging. Trial Registration: ClinicalTrials.gov: NCT01679977.